The Role of Platelet-Rich Plasma Therapy in Treating Sports Injuries - Damian Machaj; Aleksandra Mazurek; Dominik Machaj; Wiktoria Józefowicz (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Sports injuries are a significant health problem for both professional and recreational athletes. Standard treatment methods, including physiotherapy, pharmacotherapy, and surgical interventions, often fall short in cases of severe soft tissue damage. This has led to a growing interest in alternative therapies, such as platelet-rich plasma (PRP). In recent years, there has been growing interest in platelet-rich plasma (PRP) therapy due to its potential regenerative properties. PRP is increasingly used in the treatment of sports injuries, with the aim of accelerating tissue regeneration and facilitating a return to full physical fitness. This paper attempts to analyze available scientific studies to assess the effectiveness of PRP in the treatment of sports injuries.   Purpose of the work: The aim of this study is to assess the effectiveness and safety of platelet-rich plasma (PRP) therapy in treating sports-related muscle, tendon, ligament, and joint injuries, and to compare its efficacy with other established treatment modalities, such as physiotherapy and pharmacotherapy. Results: Platelet-rich plasma (PRP) therapy has been shown to be highly effective in treating sports injuries, particularly muscle and tendon injuries. PRP accelerates tissue regeneration and shortens the time to return to physical activity, but the effectiveness of the therapy depends on the proper preparation protocol and individual patient characteristics. Compared to other treatment methods, PRP has a favorable safety profile and a lower risk of complications. Despite promising results, further studies are needed to better determine the long-term effectiveness and optimal conditions for using this therapy.